Online Rehabilitation Protocols for Medial Patellofemoral Ligament Reconstruction With and Without Tibial Tubercle Osteotomy Are Variable Among Institutions - Reed G. Coda, B.S; Sana G. Cheema, B.A; Christina Hermanns, B.S; Meghan Kramer, D.P.T; Armin Tarakemeh, B.A; John P. Schroeppel, M.D; Scott Mullen, M.D; Bryan G. Vopat, M.D; Mary K. Mulcahey, M.D (Elsevier, 2021)
Purpose: To compare and contrast the various rehabilitation protocols for medial patellofemoral ligament (MPFL) reconstruction and MPFL reconstruction plus tibial tubercle osteotomy (TTO) published online by academic orthopaedic surgery residency programs and private practice institutions throughout the United States. Methods: We performed a systematic electronic search of MPFL reconstruction rehabilitation protocols in academic orthopaedic surgery residency programs in the United States using Google's search engine (www.google.com) based on the Fellowship and Residency Electronic Interactive Database Access System (FREIDA). Private practice organizations publishing MPFL reconstruction or MPFL reconstruction-TTO rehabilitation protocols that were found on the first page of search results were also included, but no comprehensive search for private practice protocols was performed. Protocols specifying an MPFL reconstruction with TTO were included for separate review because of altered weight-bearing status postoperatively. A list of comparative criteria was created to assess the protocols for the presence and timing of the various rehabilitation components. Results: From the list of 189 U.S. academic residency programs, as well as additional private practice protocols found in the Google search, 38 protocols were included for review (31 protocols for isolated MPFL reconstruction and 7 protocols for MPFL reconstruction plus TTO). A return to full range of motion by week 6 was recommended by 15 (48.4%) of the isolated MPFL reconstruction protocols and 6 (85.7%) of the MPFL reconstruction-TTO protocols. Six weeks of knee brace wear was recommended by 13 isolated MPFL reconstruction protocols (43.3%) and 4 MPFL reconstruction-TTO protocols (57.1%). Moreover, 6 isolated MPFL reconstruction protocols (19.4%) and 3 MPFL reconstruction-TTO protocols (42.9%) recommended use of a patellar stabilizing brace postoperatively. Conclusions: There is substantial variability among rehabilitation protocols after MPFL reconstruction, as well as MPFL reconstruction plus TTO, including postoperative range of motion, weight-bearing status, and time until return to sport. Furthermore, many online protocols from academic orthopaedic surgery residency programs and private practices in the United States fail to mention several of these parameters, most notably functional testing to allow patients to return to sport. Clinical Relevance: Proper rehabilitation after MPFL reconstruction with or without TTO is an important factor to a patient's postoperative outcome. This study outlines the variability in online rehabilitation protocols after MPFL reconstruction with or without TTO published online by academic residency programs and private practice institutions.